Prices vs. Quantities - Weitzman, Martin L. (Review of Economic Studies, 1974)
Journal Article Prices vs. Quantities Get access Martin L. Weitzman Martin L. Weitzman Massachusetts Institute of Technology Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 41, Issue 4, October 1974, Pages 477–491, https://doi.org/10.2307/2296698 Published: 01 October 1974